A Conflict Resolution Learning Models using Carton Ekspression Card Media in Developing Conflict Resolving Skill in Elementary School - Dewi, Sinta Maria; Tarpan Suparman; Yulistina Nur DS; Tia Latifatu Sa’diyah; Ayu Fitri (Universitas Pendidikan Ganesha, 2023)
The peace of students in school in reality is not easy to realize. Indications that connotes not being peaceful at school are increasingly obvious. Various conflicts, ranging from the simplest form, namely verbal behavior, to more serious violence with a physical dimension in the form of brawls, persecution, and even murder have been committed by some students in schools. The purpose of this paper is to explain the study of the need for a conflict resolution learning model with cartoon expression card media in developing students' problem-solving skills in elementary school. This research method consists of several steps, namely research design, subject research, data collection instruments and data analysis. Based on the results of research and discussions that have been carried out, data conclusions were obtained about students' initial ability to resolve conflicts that often occur in grade 5 at the elementary school level, namely from 4 schools categorized in the group of students' initial ability to resolve conflicts still need to be improved because the achievement is relatively low. Data were produced on the needs analysis study of conflict learning models with children's conflict cartoon expression card media based on questionnaires and the results of interviews stated that there was no specific model or strategy in order to learn about conflicts and how to handle them. In the end, it is stated by teachers and students that a special model based on conflict handling is needed. Through this model, it is hoped that teachers have alternatives that can be used as part of the learning process itself. Even students stated that such a model is needed to provide understanding to each student so as not to easily conflict.